Remote ischemic preconditioning in patients with intermittent claudication (Clinics, 2013)
OBJECTIVE: Remote ischemic preconditioning (RIPC) is a phenomenon in which a short period of sub-lethal ischemia in one organ protects against subsequent bouts of ischemia in another organ. We hypothesized that RIPC in patients with intermittent claudication would increase muscle tissue resistance to ischemia, thereby resulting in an increased ability to walk. METHODS: In a claudication clinic, 52 ambulatory patients who presented with complaints of intermittent claudication in the lower limbs associated with an absent or reduced arterial pulse in the symptomatic limb and/or an ankle-brachial index